Perceptions of interprofessional collaborative practice in South Africa: A systematic review - Nadia Mohamed; Craig W. Peck; Janine Senekal (AOSIS, 2024)
Background: Interprofessional education (IPE) and interprofessional collaborative practice (IPCP) were developed to address the health needs of communities through collaborative practice across healthcare disciplines. The impact of IPE on IPCP and clinical service delivery in South Africa is not evident, possibly because of the lack of IPCP experiences among healthcare professionals. Aim: International literature reports facilitators and barriers of IPCP implementation, but there was a need to filter the evidence to identify literature from the South African context regarding the perceptions of healthcare workers' perceived barriers and facilitators of IPCP. Setting: South African literature. Methods: A systematic review was conducted to synthesise evidence from articles published between January 2017 and December 2021. Only qualitative studies targeting health professionals in South Africa who had been exposed to IPCP were included. Consistent with Preferred Reporting Items for Systematic reviews and Meta-Analysis, a multi-database search yielded 424 articles, which were screened for relevance and appraised for quality using the Critical Appraisal Skills Programme (CASP) tool. A thematic synthesis of the findings was conducted by applying ethical principles. Results: Synthesis of barriers and enablers for IPCP implementation in the South African context included key aspects of healthcare systems, management and team leadership. Conclusion: The integration of IPCP into clinical practice in South Africa is still limited as healthcare professionals operate in silos. Contribution: Recommendations of this study include greater integration of services combined with competent management and visionary leadership, together with the incorporation of IPE into undergraduate professional training programmes.